Biochemical profile of cattle with left displacement of the abomasum: energy balance, uric acid, electrolyte levels, and metabolic relationships - Suvarikli-Alan, Beyza; İder, Merve; Altunok, Vahdettin; OK, Mahmut; Camgöz, Avni (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Left displacement of the abomasum (LDA), which affects the production performance of high-yielding cows and is frequently manifested in the early postpartum period, leads to significant changes in the metabolism of cows. Methods: This study aimed to investigate the changes in biochemical parameters and the correlations between these parameters in dairy cattle with left displacement of the abomasum. The material of the present study consisted of twenty healthy cows and twenty-eight dairy cows with LDA. The serum was analysed for twenty-five different biochemical parameters. Results: The levels of glucose, triglycerides, gamma-glutamyl transferase (GGT), aspartate aminotransferase (AST), haptoglobin, β-hydroxybutyrate, NEFA, and amylase enzyme activity were significantly elevated (p<0.05) in cows with left displacement of the abomasum compared to healthy cows. Their levels of uric acid, total protein, albumin, potassium, calcium, chlorine, magnesium, phosphate, cholesterol, and HDL significantly lowered (p<0.05). The study’s results indicated that NEFA was positively correlated with β-hydroxybutyrate concentrations. HDL was positively correlated with albumin and cholesterol levels. Calcium was positively correlated with albumin, phosphorus, magnesium, and chlorine concentrations. A positive correlation was found between uric acid and NEFA, albumin, phosphorus, magnesium, HDL, and cholesterol concentrations. The results showed that the biochemical parameters of cattle with LDA changed, and the identified correlations were associated with metabolic disorders, including negative energy balance, fatty liver, and ketosis in LDA cases. Furthermore, the correlation between uric acid levels and metabolic markers in cows with LDA supports the link between the disease and energy metabolism and liver dysfunction. Conclusion: It was concluded that maintaining postpartum energy balance, electrolyte balance, and calcium homeostasis in dairy cows is crucial for preventing abomasal displacement and for evaluating biochemical parameters accordingly.